Genes and common diseases - Wright, Alan F., MRC; Hastie, Nicholas; Cambridge eBooks (Cambridge : Cambridge University Press, 2007)
Genes and Common Diseases presents an up-to-date view of the role of genetics in modern medicine, reflecting the strengths and limitations of a genetic perspective. The current shift in emphasis from the study of rare single gene disorders to common diseases brings genetics into every aspect of modern medicine, from infectious diseases to therapeutics. However, it is unclear whether this increasingly genetic focus will prove useful in the face of major environmental influences in many common diseases. The book takes a hard and self-critical look at what can and cannot be achieved using a genetic approach and what is known about genetic and environmental mechanisms in a variety of common diseases. It seeks to clarify the goals of human genetic research by providing state-of-the art insights into known molecular mechanisms underlying common disease processes while at the same time providing a realistic overview of the expected genetic and physiological complexity.
Part I. Introductory Principles: 1. Genes and their expression Dirk-Jan Kleinjan; 2. Epigenetic modification of chromatin Donncha Dunican, Sari Pennings and Richard Meehan; 3. Population genetics and disease Donald Conrad and Jonathan Pritchard; 4. Mapping common disease genes Naomi Wray and Petter Visscher; 5. Population diversity, genomes and disease Gianpiero Cavalleri and David Goldstein; 6. Study design in mapping complex disease traits Harry Campbell and Igor Rudan; 7. Diseases of protein misfolding Christopher Dobson; 8. Aging and disease Thomas Perls; 9. The MHC paradigm -- genetic variation and complex disease Adrian Kelly and John Trowsdale; 10. Lessons from single gene disorders Nicholas Hastie; 11. Environment and disease A.J. McMichael and K.B.G. Dear; 12. Contemporary ethico-legal issues in genetics Renate Gertz, Shawn Harmon and Geoffrey Pradella; Part II. Common Medical Disorders: 13. Developmental disorders Stephen Robertson and Andrew Wilkie; 14. Genes, environment and cancer Timothy Bishop; 15. The polygenic basis of breast cancer Paul Pharoah and Bruce Ponder; 16. TP53: a master gene in normal and tumour suppression Pierre Hainaut; 17. Genetics of colorectal cancer Susan Farrington and Malcolm Dunlop; 18. Genetics of autoimmune disease John Bell and Lars Fugger; 19. Susceptibility to infectious diseases Andrew Walley and Adrian Hill; 20. Inflammatory bowel diseases Jean-Pierre Hugot; 21. Genetic anaemias W.G. Wood and D.R. Higgs; 22. Genetics of chronic disease: obesity Sadaf Farooqi and Stephen O'Rahilly; 23. Type 2 diabetes mellitus Mark McCarthy; 24. Genetics of coronary heart disease Rossi Naoumova, Stuart Cook, Paul Cook and Timothy Aitman; 25. Genetics of hypertension B. Keavney and M. Lathrop; 26. Obstructive pulmonary disease Bipen Patel and David Lomas; 27. Skeletal disorders Robert Colbert; 28. The genetics of common skin diseases Jonathan Rees; 29. Molecular genetics of Alzheimer disease and other adult-onset dementias Peter St George-Hyslop; 30. Major psychiatric disorders in adult life Amanda Elkin, Sridevi Kalidindi, Kopal Tandon and Peter McGuffin; 31. Speech and language disorders Gabrielle Barnby and Anthony Monaco; 32. Common forms of visual handicap Alan Wright; 33. Genetic and environmental influences on hearing impairment Karen Steel; 34. Pharmacogenomics -- clinical applications Gillian Smith and Roland Wolf.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Medical genetics; Electronic books